2010
DOI: 10.1111/j.1365-2222.2010.03586.x
|View full text |Cite
|
Sign up to set email alerts
|

How do teenagers manage their food allergies?

Abstract: A significant number of teenagers demonstrate risk-taking behaviour in the management of their food allergies. Teenagers also felt it would be helpful for their peers to be educated about food allergy. This novel strategy might help them to avoid trigger foods and enable teenagers to access help more readily if they suffer a reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(210 citation statements)
references
References 31 publications
5
194
0
11
Order By: Relevance
“…8,9 An unexpected, worrisome finding in this study is that 11% of milk, egg, or peanut reactions resulted from these exposures. In some cases, reactions occurred to a food that was given in a larger amount than before, which is a nuance worth considering when taking a medical history of young children with possible The annualized rate or reactions for all foods was 0.81 (95% CI: 0.76-0.85).…”
Section: Figurementioning
confidence: 82%
See 2 more Smart Citations
“…8,9 An unexpected, worrisome finding in this study is that 11% of milk, egg, or peanut reactions resulted from these exposures. In some cases, reactions occurred to a food that was given in a larger amount than before, which is a nuance worth considering when taking a medical history of young children with possible The annualized rate or reactions for all foods was 0.81 (95% CI: 0.76-0.85).…”
Section: Figurementioning
confidence: 82%
“…4 Errors in daily management can result in allergic reactions and undertreatment of severe reactions. [5][6][7][8][9][10][11][12][13][14][15][16] The primary aim of this study was to determine the frequency and circumstances of allergic reactions to foods, and treatment responses, in a prospective study of infants and preschoolaged children with likely egg or milk allergies. The cohort we examined is participating in an observational study on the natural course of milk/egg allergy and is being observed for the development of peanut allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da importância do tema, ainda existem poucos estudos neste sentido, sendo que a maioria aborda grupos de pacientes com alta prevalência de alergia a amendoim e/ou frutas oleaginosas [3][4][5][6][7][8][9] . Por outro lado, em nosso país, o leite de vaca é um dos principais alérgenos nesta faixa etária e sua exclusão é extremamente difícil, por sua ampla distribuição em produtos alimentícios e sua importância nutricional na alimentação da criança e mesmo assim, não se encontram trabalhos onde se abordem os problemas relacionados a essa restrição.…”
Section: Introductionunclassified
“…Long-term management is focused on the avoidance of the foods that trigger the allergic reactions, which in turn places a psychological burden on patients and carers that can result in stress and anxiety. There is, in addition, often further anxiety relating to the burden of managing acute reactions -particularly if the decision to administer adrenaline (epinephrine) also falls on the patient and/or carer (3)(4)(5)(6). In some cases, this can have a considerable impact on the day-to-day lives of patients and carers (7).…”
mentioning
confidence: 99%